Language Acquisition: The Influential Factors and Its Connection With Age - Dony Marzuki (Politeknik Negeri Padang, 2012)
The term of language acquisition often leads to a misinterpretation when it deals with English learning. However, there is one distinct point that might be pointed out about language acquisition which differentiates it with the general language learning. Language acquisition is the process of acquire language while language learning is the process of learning the language. This article is meant to give a perspective about language acquisition, factors that influence the acquisition and also the connection of language acquisition with age.